2011
DOI: 10.1590/s0034-72802011000400007
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da demanda e morbidade dos pacientes atendidos em centro de urgências oftalmológicas de um hospital universitário

Abstract: and the approaches adopted. Results: 8.346 patients were assisted, 3.819 female (45,79%) and 4.521 male (54,20%). The ages ranged from 0 to 100 years and the most common group of occupations was general services (24,20%). The most frequent diagnosis was conjunctivitis (27,91%). The most common measure taken was the drug treatment (65,5%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
2
3
1
5
Order By: Relevance
“…In this study, the foreign body was identified as the third main cause of red eye, and trauma was present only in 3.1% of cases. These findings are in agreement with the work of Pereira et al (7), which identified conjunctivitis (27.91%) and foreign body (12.86%) as the main causes of red eye, with ocular trauma showing little expression (2.23%). Possibly the low percentage of trauma as a cause of red eye is due to the existence of referral hospitals of trauma and multiple trauma in the city of Belo Horizonte, and due to the difficult access to Fundação Hilton Rocha by public transportation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, the foreign body was identified as the third main cause of red eye, and trauma was present only in 3.1% of cases. These findings are in agreement with the work of Pereira et al (7), which identified conjunctivitis (27.91%) and foreign body (12.86%) as the main causes of red eye, with ocular trauma showing little expression (2.23%). Possibly the low percentage of trauma as a cause of red eye is due to the existence of referral hospitals of trauma and multiple trauma in the city of Belo Horizonte, and due to the difficult access to Fundação Hilton Rocha by public transportation.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, there was a predominance of females, diverging from the results of other epidemiological studies that reported the male gender as predominant: 72% by Araujo et al (4), 64,84% by Rocha et al (5), 66% by Kara-Junior et al (6), 54,2% by Pereira et al (7), 89% by Cecchetti et al (13). The reason for this discrepancy has not been clarified.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Estudos apresentam que em torno de 50% dos pacientes que buscam serviço de urgência oftalmológica apresentam história de trauma. No presente estudo os casos de emergência oculares, incluindo trauma, queimaduras, corpo estranho, irritação, representaram 48% dos atendimentos (PEREIRA et al,2011).…”
Section: Resultsunclassified